(untitled) - Kiev, Ari (New York, 2002)
The Psychology of Risk is equally vital for everyone from the day trader to short-term online trader to long-term investor. A clear, enjoyable insight into what makes trading success.
Keywords: Investments,Portfolio management,Risk management,Đầu tư,Quản lý danh mục đầu tư,Quản lý rủi ro; Psychological aspects,Khía cạnh tâm lí